La politique de prévention contre le dopage en Espagne en question - Bourlon-Buon, Y. H.; Pardo, R. (Movement & Sport Sciences - Science & Motricité, 2016)
Doping phenomenon forces sports organizations to implement prevention policies to combat doping behaviors. We have analyzed their orientations from the point of view of the athletes and their coaches interviewed in cycling, athletics and basketball. We noted the lack of specific prevention measures and the imposition of those portrayed by the media. This situation puts in vulnerable position young athletes who find neither their coaches nor their families enough information. In this sense, the remembered information is vague and focus on sanctions rather than harmful effects on health or development of the ethical-moral aspect.